2015
DOI: 10.1002/pssa.201532136
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and double‐hierarchical structure of MoS2/C nanospheres

Abstract: The results of MoS 2 /carbon nanocomposite hydrothermal synthesis is presented. The synthesized material was studied by XRD, TEM, EDS, SAXS, and porosimetry. The multilayer nanospheres with the average size 40-70 nm were obtained. The investigations confirm the formation of particles with double-hierarchical structure where 2H-MoS 2 layers alternate with carbon layers. Atomic ratio of MoS 2 :C is about 1:1 (at.%) and does not depend on the heat treatment.The proposed formation mechanism of MoS 2 /C doublehiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The synthesis procedure was based on the hydrothermal method described in [ 15 ]. XRD study confirmed the formation of 2H-MoS 2 (P63/mmc) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis procedure was based on the hydrothermal method described in [ 15 ]. XRD study confirmed the formation of 2H-MoS 2 (P63/mmc) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…MoS 2 coating has good self-lubricating properties that can be attributed to the proper combination of grain size, two-crystal orientation, and absence of contaminants [4][5][6][7]. The MoS 2 coating under ultra-high-pressure conditions has a coefficient of friction of 0.001 [8,9]. However, the porous columnar structure of pure MoS 2 coating results in low hardness, low load-carrying capacity, poor film-based bonding properties, and easy tribochemical reaction with air, which limit the practical applications of the MoS 2 coating [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mesoporous carbon does not only have a large surface area providing the EDL capacity, but also keeps connected and prevents the exfoliation of MoS 2 during the charge/discharge process. 2-, the whole process lasted at 220 °C for 24 hours in a Teflon autoclave [8]. Additionally, the obtained material was annealed in argon atmosphere at 500 °C for 2 hours.…”
Section: Introductionmentioning
confidence: 99%